ANALISIS PENGARUH NEGATIF PENGGUNAAN MEDIA SOSIAL TERHADAP HASIL BELAJAR PENDIDIKAN AGAMA ISLAM - Sulasmi, Andi; Bayu, Yunus (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
Research spreads the use of social media among grade IX students of SMPN 4 Malangke is growing rapidly. That social media is generally used by students to find new friends and as a means of communicating with friends who are far away. However, this development has a significant influence on the learning process in the classroom. This study uses an ex-post facto approach, which means that data collection is carried out after all the events or facts studied have occurred without any intervention or treatment from the researcher. The data in this study were collected through three main methods, namely: questionnaires, interviews, and documentation studies. The PAI learning outcomes of grade IX students of SMP Negeri 4 Malangke showed a decline in achievement. This is strongly suspected to be related to the negative impact of the use of social media which affects PAI learning values. The use of social media by grade IX students of SMP Negeri 4 Malangke has a negative influence on their learning outcomes. This conclusion is supported by the results of statistical calculations using t-test analysis. The t-count value (7.942) was obtained which was greater than the t-table value (2.042), so the null hypothesis (H₀) was rejected. Thus, it can be concluded that there is a significant influence between the use of social media on the learning outcomes of grade IX students of SMP Negeri 4 Malangke. In the context of this study, the influence is negative.